THE ROLE OF SUSTAINABLE TOURISM IN THE DEVELOPMENT OF THE REGIONAL ECONOMY (International Journal of Innovative Technologies in Economy, 2023)
The subject of sustainable tourism is being increasingly discussed in recent years because there is a growing recognition of the intricate connection between the environment and the economy. It is crucial to integrate these two components in order to establish a foundation for long-term development that has a positive impact on society as a whole. The tourism industry is experiencing a paradigm shift and this presents challenges that need to be addressed by the relevant authorities and economic stakeholders. It is imperative to guide the industry towards sustainable development in order to tackle these challenges. Based on these findings, our research aims to emphasize the role of tourism in regional development, as well as to measure the impact of intensive and extensive tourism on environmental factors. This will be done through the use of qualitative and quantitative indicators, highlighting the fact that environmental damage ultimately hampers economic growth. The results of our research will enable us to propose several actions that should be taken by both developed and less developed regions to enhance tourism activity while respecting the environment. In conclusion, sustainable tourism is an important topic that requires attention due to the intertwined relationship between the environment and the economy. The tourism industry is undergoing changes that necessitate the implementation of sustainable practices. Our research will analyze the role of tourism in regional development and assess its impact on the environment. These findings will then be used to formulate actionable steps to promote tourism while protecting the environment.